Pengembangan Produk Olahan Hasil Pertanian Tidak Layak Jual Pepaya APeS dan Pisang KeMPeS - Febriansyah, Febriansyah; Oktavianus, Donny; Nasrullah, Abdi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: This research aims to develop value-added processed products from previously unsellable agricultural produce, namely papaya and bananas, including Papaya-based Abon, Permen (candies), and Selai (jams) or APeS, and Banana-based Keripik (chips), Molen (banana fritters), Permen (candies), and Sale (sugar-coated snacks) or KeMPeS, within the Small and Medium Enterprises (UMKM) sector of Banana Chips in Penantian Village. The research primarily focuses on the utilization of digital marketing strategies as the key tool for marketing these products. Methodology/approach: The research method employed product development experiments and the implementation of digital marketing strategies. Data collection involved surveys, interviews, observations, and market analysis. The results indicate that the developed papaya-based APeS and banana-based KeMPeS products have successfully enhanced the value of previously unsellable agricultural produce. Furthermore, the implementation of digital marketing strategies has proven effective in increasing the visibility and sales of UMKM Banana Chips' products in the digital marketplace. Results/findings: The results indicate that the developed papaya-based APeS and banana-based KeMPeS products have successfully enhanced the value of previously unsellable agricultural produce. Furthermore. Limitation: This research suggest that UMKM in similar regions can leverage similar strategies to develop processed agricultural products and enhance market access through digital platforms. Contribution: This research offers a positive contribution to the development of UMKM in Penantian Village and provides valuable insights into the utilization of digital marketing to support local economic growth.